2007
DOI: 10.1111/j.1365-2214.2007.00780.x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal punishment practices in a rural area of Turkey

Abstract: These findings can be useful in establishing parental educational programming that is directed at decreasing the rates of punishment practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
3
0
1
Order By: Relevance
“…In other words, while the responsibility to implement discipline provided relative familial control and power to Saraycık women, they also recognized themselves as feeling persons who were victims of violence in their relationships with men. This recognition might have contributed to their awareness that physical punishment of children constitutes violence (Buldukog ˘lu & Kukulu, 2008). Although women reported being angry with their children, interpretative repertoires such as women as failing mothers, mothers as helpless victims of strong emotions, monster moms, and weak disciplinarians suggested guilty feelings.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, while the responsibility to implement discipline provided relative familial control and power to Saraycık women, they also recognized themselves as feeling persons who were victims of violence in their relationships with men. This recognition might have contributed to their awareness that physical punishment of children constitutes violence (Buldukog ˘lu & Kukulu, 2008). Although women reported being angry with their children, interpretative repertoires such as women as failing mothers, mothers as helpless victims of strong emotions, monster moms, and weak disciplinarians suggested guilty feelings.…”
Section: Discussionmentioning
confidence: 99%
“…Bir çok ül ke de, çe şit -li kül tür ler de fi zik sel ce za lan dır ma, ka tı di sip lin yön tem le ri nin kul la nıl ma sı, ya sal ve kül tü rel olarak ka bul edi le bi lir sa yıl mak ta dır. 8,[15][16][17][18] Üze rin de tam ola rak uz la şıl mış ol ma sa da, ba zı uz man la ra gö -re, ço cuk ta iz bı rak ma ya cak, ya ra lan ma ya se bep olma ya cak de re ce de fi zik sel şid det uy gu lan ma sı is tis mar kap sa mın da de ğer len di ril me me li dir. Baş -ka bir de yiş le "iz bı ra ka cak ka dar şid det li vu rul ması " is tis ma ra yol açan dav ra nış lar ara sın da ka bul edil mek te dir.…”
Section: Ka Ti Lim CI Nin Ki̇m Li̇ ğİ Ni̇n Alin Ma Si Ve Bi̇l Di̇ Ri̇m Zo Runclassified
“…Another study indicated that slightly more than a third of parents admitted to using physical discipline with their infants (under 1 year old), while 94% reported employing such methods with toddlers aged 3 to 5 (Straus & Stewart, 1999). In a Turkish study, it was observed that all participating mothers resorted to various forms of punishment, with physical punishment being the predominant method employed (Buldukoglu & Kukulu, 2008). Buldukoglu and Kukulu (2008) further noted that, from a traditional Turkish perspective, many parents consider corporal punishment a legitimate and effective means of discipline.…”
Section: Introductionmentioning
confidence: 99%
“…In a Turkish study, it was observed that all participating mothers resorted to various forms of punishment, with physical punishment being the predominant method employed (Buldukoglu & Kukulu, 2008). Buldukoglu and Kukulu (2008) further noted that, from a traditional Turkish perspective, many parents consider corporal punishment a legitimate and effective means of discipline. Indeed, corporal punishment is often perceived as socially acceptable and normative within Turkish parenting practices.…”
Section: Introductionmentioning
confidence: 99%